Answer:
Explanation:
General form of the linear differential equation can be written as:
![(dy)/(dx)+P(x)y=Q(x)](https://img.qammunity.org/2023/formulas/mathematics/college/1jzunlcfpl8p50o70hi3iaptn4bi53ubg9.png)
For this case, we can rewrite the equation as:
![(dy)/(dx)+(1)/(2x)y=(√(x))/(x)](https://img.qammunity.org/2023/formulas/mathematics/college/upyudnccvzm80nxef7plbddhnxvddsc3t6.png)
Here
![P(x) =(1)/(2x); Q(x)=(√(x))/(x)](https://img.qammunity.org/2023/formulas/mathematics/college/l5bmta6v49im3xxbaoy5n8jixjstminwj8.png)
To find the solution (y(x)), we can use the integration factor method:
![Fy(x)=\int Q(x)Fdx+C \rightarrow F=e^{\int P(x)dx](https://img.qammunity.org/2023/formulas/mathematics/college/k6coikuiyk6d3ipl5g46egprg0t06q7v9t.png)
Then
![F=e^{\int (1)/(2x)dx}=e^x=√(|x|)](https://img.qammunity.org/2023/formulas/mathematics/college/efwu1qc8aavvsb4pfr9jkp40673jas03i6.png)
So, we can find:
![y√(|x|)=\int (√(x)√(|x|))/(x)dx+C](https://img.qammunity.org/2023/formulas/mathematics/college/u2o2qlaeejqsvxick8rglbgd0azob6c7d2.png)
Suppose that
, then
, and we find:
![y√(x)=x+C \rightarrow y(x)=√(x)+(C√(x))/(x)](https://img.qammunity.org/2023/formulas/mathematics/college/qd90o9aw3e7s7khp0iut9txjbyzr8pbzop.png)
To check our solution is right or not, put your y(x) back to the ODE:
![y' = (1)/(2√(x))-\frac{C}{2\sqrt{x^(3)}}](https://img.qammunity.org/2023/formulas/mathematics/college/kfz38mo1rwzr1iqqldr477uj3r6blxxz8w.png)
![2xy'=(x-C)/(√(x))](https://img.qammunity.org/2023/formulas/mathematics/college/3kp9h835q6zrzpwukxcfomhsmco1569cig.png)
![2xy'+y=(x-C)/(√(x))+√(x)+(C√(x))/(x)=2√(x)](https://img.qammunity.org/2023/formulas/mathematics/college/dt9gn91jxwqqpl6nohbqb0u3hljcug8an0.png)
(it means your solution is right)